Effect of stacking sequence on the tribological behaviour of jute-glass hybrid epoxy composite. (2020) - Acharya, S.K.; Bera, Tanusree; Prakash, Ved; Pradhan, Subhrajit
Abstract: In the present work, an attempt has been made to study the three body abrasive wear behaviour of laminate hybrid composites consisting jute fiber/glass fiber reinforced with epoxy resin. The composites samples with different stacking sequence like S1 (GJJJJJJJJG), S2 (GJGJGGJGJG) and S3 (JGJGJJGJGJ) with glass (G) and jute (J) were fabricated using hand layup technique. The three-body abrasive wear behaviour of the designed hybrid composite was carried out as per ASTM G65 standards. The results indicate that the S2 composite exhibits higher wear resistance among the developed composites. The scanning electron microscope (SEM) study was performed for the worn surfaces of the composites to find out the wear mechanism.